Statistical review of microstructure-property correlation of stainless steel: implication for pre- and post-weld treatment - Muhammed, Musa; Mustapha, Mazli; Ginta, Turnad Lenggo; Ali, Abdullah Musa; Mustapha, Faizal; Hampo, Chima Cyril (MDPI, 2020)
first_pagesettingsOrder Article Reprints Open AccessReview Statistical Review of Microstructure-Property Correlation of Stainless Steel: Implication for Pre- and Post-Weld Treatment by Musa Muhammed 1,Mazli Mustapha 1,*,Turnad Lenggo Ginta 1,Abdullah Musa Ali 2,Faizal Mustapha 3 andChima Cyril Hampo 1ORCID 1 Department of Mechanical Engineering, Universiti Teknologi PETRONAS, Seri Iskandar 32610, Perak, Malaysia 2 Department of Geology, Bayero University Kano (BUK), Kano 700241, Nigeria 3 Department of Aerospace Engineering, UPM, Serdang 43000, Selangor, Malaysia * Author to whom correspondence should be addressed. Processes 2020, 8(7), 811; https://doi.org/10.3390/pr8070811 Received: 15 June 2020 / Revised: 29 June 2020 / Accepted: 2 July 2020 / Published: 10 July 2020 (This article belongs to the Special Issue Selected Paper from ICPER-2020 (7th International Conference on Production, Energy and Reliability)) Downloadkeyboard_arrow_down Browse Figures Versions Notes Abstract For the past three centuries, there has been a very high demand for stainless steel for different applications, due to its corrosion resistance coupled with the good strength and low cost of the metal. Several welding techniques have been adopted in the fabrication of stainless steel, with the choice of welding technique hinged on the desired requirements. Advancement has been made in its dissimilar welding with other metals like aluminum, copper and titanium. While similar welding of stainless steel faces the challenge of weld metal property deterioration, dissimilar welding poses more serious challenges due to the differential in chemical composition and the thermophysical properties of the base metals. A review of the literature reveals that considerable progress has been made in the improvement of the properties of the weld joint by the application of several weld treatment processes. It was discovered that most of the researchers focused on the effect of these weld treatment processes on the properties of the weld joints, with little attempt to establish a relationship between the microstructure and properties. This review paper critically analyzed the effect of weld treatment processes on the properties of stainless steel in light of microstructure-property correlation.